Interelaciones en el aprendizaje en estudiantes del noveno año de edcuacion básica del colegio Nacional Técnico Ing. José Corsino Cardenas cantón pasaje provincia del Otro - Puglaa Sagbay, Patricia Pilar (2013)
This research work includes helpful information aimed at meeting the needs of knowledge, and the importance of allowing the interrelation in the process of teaching and learning, study has been made in the Technical College Ing . José Cárdenas Corsino city Passage, 2012 school year - 2013. Education is a human act, hence, the learner and the educator are members of a community and its encounter takes place under the same context, from which derives every relationship, in essence is a form of communication, which focuses on conflict, fight and understanding. The teacher should observe the relationships established in the class group and intervene to encourage you to analyze and resolve conflicts that arise in the group, in a climate of acceptance, mutual aid, cooperation and tolerance.arning is a process of appropriation of accumulated historical cultural experiences through which the student becomes personality, because through the activity it performs and the relationship he has with the environment in which it develops, will appropriating knowledge, is where the need for this research which brews acquired by the student in the classroom should be with similar characteristics between each student and teacher arises, so that learning is only achieved when making this process of interaction that allows seize knowledge, which regulates their activity and expressed what they learned. The present investigation we considered general objective: To determine the incidence of the interrelationships in the process of learning between teachers and students in the ninth year of basic education. To do the field work consisted of an interview to Students and Teachers in an interview this year was conducted basic education. It was concluded that the relationship between student and teacher is limited, because there is no empathy between stakeholders in education, lacking this aspect is standing a barrier to learning and becoming a pure traditionalism. It is here that this proposal arises to achieve intervene with the necessary tools to harmonize the communication activity between education actors and these should be listed in daily in every living process between teacher and student, also used in the classroom active learning strategies proposed by Piaget Vygotsky, Ausubel and Brunner and others posed activation of the Zone of Proximal Development.